(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article focuses on identifying the importance of relationships between the principal and teaching staff in forming a healthy psychological environment within general education school management. It emphasizes strengthening factors such as human relationships, trust, collaboration, and emotional support in management practices. The clarified area of the article is defined as the extent of the principal’s influence on the formation of the social environment within the pedagogical team.